Anime's Performativity: Diversity through Conventionality in a Global Media-Form. (March 2017) - Suan, Stevie
Anime is a globally prominent media-form with a multitude of styles, yet it maintains a relative uniformity to sustain a recognizable identity as a particular category of media. The performance of the recognizably 'anime-esque' is what distinguishes anime as a type of animation, allowing it to be sold and consumed as 'anime'. Anime, and its recognizable identity, are performatively constituted by a series of anime-esque acts performed in animation, citing a system/database of conventionalized models in each iteration. What we recognize as 'anime proper' are not just 'animations from Japan', but animations that perform large quantities of anime-esque acts. However, anime must continuously work through the problematic of maintaining its identity without redundancy, each performance working through the tensions of diversity and uniformity: in straying too far from a conventional model, it loses anime-esque recognizability and cannot be sold/consumed as anime. As such, anime's identity negotiates the dynamic divisions between uniformity, repetition and the global on the one hand, and diversity, variation and the local, on the other. Working through this problematic entails a different type of creativity as combinations of citations from conventional models in each performance negotiate that particular anime's identity as an anime production and its distinction from other anime. Anime's problematic is not only invoked through the engagement of conventionalized models of character design and narrative, but also in the technical processes/materiality of animation, which cite character models and conventionalized acting expressions when animated. Yet it is not just the material limits of the medium of animation. There is another limit in the performance of anime in the act of citation that facilitates the doing (and selling) of anime: in the repeated acts of the anime-esque, in the serialization of anime as a media-form, the contours of anime's formal system become a factor of convergence.